DEVELOPMENT OF A WIRELESS DEVICE FOR AUTOMATIC ALERT OF A CRYING BABY (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The article presents the development of a wireless device for automatic notification of a baby's crying. The aim of the work is to create a system capable of recording the sound of crying using a sound sensor and transmitting a signal to the parental home or another responsible person via wireless technologies such as Bluetooth or Wi -Fi.The article includes consideration of the components of the system components: microcontrollers (Arduino Uno and Arduino Nano), sound sensors and communication modules. The selection criteria for each component, its technical characteristics and features are considered. The technological process of assembling the device is also described, including design, soldering, programming and testing. The results of the work show that the proposed device can effectively implement its function of providing reliable notification to parents about the crying of the child, which will increase the level of safety and comfort at home.